2023
DOI: 10.1126/scitranslmed.ade3341
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide enhances natural killer cell function and yields remissions in patients with non-Hodgkin lymphoma

Abstract: Allogeneic natural killer (NK) cell adoptive transfer has shown the potential to induce remissions in relapsed or refractory leukemias and lymphomas, but strategies to enhance NK cell survival and function are needed to improve clinical efficacy. Here, we demonstrated that NK cells cultured ex vivo with interleukin-15 (IL-15) and nicotinamide (NAM) exhibited stable induction of l -selectin (CD62L), a lymphocyte adhesion molecule important for lymph node homing. High frequencies of CD62L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Recently numerous studies focused on vitamins as new therapeutic strategies to target at metabolism underlying malignant tumour progression [7][8][9][10] .To evaluate the correlation of vitamin B3 components NA/nicotinamide (NAM) and metastasis of hepatocellular carcinoma (HCC), in vivo tumorigenicity assay were performed in C57BL/6J mice that were administered normal saline (NS), NA, or NAM respectively. We found that quite different from NAM, NA supplement suppressed tumour size in the liver and metastatic nodule numbers (Fig.…”
Section: Na But Not Nam Suppresses Hcc Growth and Metastasismentioning
confidence: 99%
“…Recently numerous studies focused on vitamins as new therapeutic strategies to target at metabolism underlying malignant tumour progression [7][8][9][10] .To evaluate the correlation of vitamin B3 components NA/nicotinamide (NAM) and metastasis of hepatocellular carcinoma (HCC), in vivo tumorigenicity assay were performed in C57BL/6J mice that were administered normal saline (NS), NA, or NAM respectively. We found that quite different from NAM, NA supplement suppressed tumour size in the liver and metastatic nodule numbers (Fig.…”
Section: Na But Not Nam Suppresses Hcc Growth and Metastasismentioning
confidence: 99%
“…PFS at 1 and 2 years was estimated at 50% and 35%, respectively. The OS at 2 years was 73% Cichocki et al [ 156 ] 4 phase I UMIN000014072 R/R CD20 + lymphoma including DLBCL ( n = 5), FL ( n = 4) PB The PBMC were culture for 3 weeks in SCGM media supplemented with IL-15 (10 ng/mL), IL-2 (5 ng/mL), anti-CD3 mAb (10–1,000 ng/mL), tacrolimus (0.1 ng/mL) and dalteparin sodium (5–10 U/mL) The final products contained 80.5% CD56 + CD3 – NK cells and 26.2 ± 11.6% of CD56 + CD3 + NKT cells 1 to 10 × 10 6 cells/kg Not disclosed Rituximab There was no AEs related to NK cells infusion Of 9 patients, seven (78%) patients achieved CR with a median duration of 44 months Tanaka et al [ 153 ] 5 phase I NCT03778619 R/R NHL including DLBCL ( n = 6), MCL ( n = 2) and MZL ( n = 1) PB CD3 depleted cells were culture in CellGro SCGM media with 1% autoplasma, irradiated autologous PBMCs, anti-CD3 mAb (10 ng/mL) and IL2 (500 IU/mL) Viability > 90% with CD16 + CD56 + NK cells > 95%, level 1:1 × 10 7 , level 2: 3 × 10 7 , level 3: 9 × 10 7 cells/kg in association with IL-2 Cyclophosphamide and fludarabine Rituximab CRS in 1 patient. GVHD, neurotoxicity, and DLTs were not observed Of 9 patients, 4 (44%) patients achieved PR, one (11%) achieved CR and 4 (44%) showed PD.…”
Section: Nk Cell Immunotherapy In Nhlsmentioning
confidence: 99%
“…Therefore, it would be interesting to observe the impact of nicotinamide on the BM adipocyte metabolism and adiposity. Furthermore, nicotinamide treatment also increases the antitumor action of NK cells in NHL patients by reprogramming their immunometabolism and increasing the CD62L expression in NHL patients 355 . Thus, it would be interesting to investigate this effect in NHL patients with obesity.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%